Music research in Angola (International Library of African Music, 1965)
Perhaps the most active of all field workers in African music at the present time is Mr. Gerhard Kubik whose articles have appeared for the past six years in our Journal. From July to December this year, 1965, he has been working in the southern part of Angola. In the south-west he recorded amongst the Vahanda and the Vahumbi tribes who seem to have affinities with the Hima peoples of the Lake regions of Central Africa. In this region he found a considerable number of instruments including chisanji mbiras, musical bows, drums and friction drums amongst others.
Keywords: African Music; Angola; Music Research